Developing Dynamic Digital Image Techniques with Continuous Parameters to Detect Structural Damage - Ming-Hsiang Shih; Wen-Pei Sung (The Scientific World Journal)
Several earthquakes with strong magnitude occurred globally at various locations, especially the unforgettable tsunami disaster caused by the earthquake in Indonesia and Japan. If the characteristics of structures can be well understood to implement new technology, the damages caused by most natural disasters can be significantly alleviated. In this research, dynamic digital image correlation method for using continuous parameter is applied for developing a low-cost digital image correlation coefficient method with advanced digital cameras and high-speed computers. The experimental study using cantilever test object with defect control confirms that the vibration mode calculated using this proposed method can highly express the defect locations. This proposed method combined with the sensitivity of Inter-Story Drift Mode Shape, IDMS, can also reveal the damage degree of damage structure. These test and analysis results indicate that this proposed method is high enough for applying to achieve the object of real-time online monitoring of structure.